Implementation Of Mapping Temporary Landsfills In Bengkulu City Based On Android - Kurnia Padila; Marhalim Marhalim; Khairullah Khairullah; Yulia Darnita (Jurnal Komputer, Informasi dan Teknologi, 2023)
Garbage is a disaster that can cause a lot of harm both in terms of the environment and health. In this incident there were many factors that affected the surrounding community, such as population density and insufficient public awareness. These factors are the main reasons for illegal waste disposal. By utilizing a Geographic Information System (GIS) implemented with Google Maps in the chaos of an Android-based temporary landfill. Data collection methods are by interview, and observation. The data obtained is to facilitate system analysis and design. The results of this study are that it can make it easier for the people of Bengkulu City to find the nearest TPS.